Translation of Metaphors from English into Russian (Based on Stephen King’s novel «The Green Mile») - Sapargalieva, A.M.; Kuldeeva, G.I. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
This article discusses the features of the translation of the author’s metaphors on the material of Stephen King’s novel «The Green Mile» and two of its translations into Russian. The article provides an analysis of metaphors in Stephen King’s novel and techniques for preserving the author’s imagery in two translations of the novel into Russian by V.A. Veber and M.V. Opaleva